Can translocations to islands reduce extinction risk for reptiles? Case studies from New Zealand. (December 2016) - Towns, D.R.; Miller, K.A.; Nelson, N.J.; Chapple, D.G.
Abstract: Globally, one in five reptile species is threatened with extinction, with invasive species a leading cause of extinction risk. Translocations could alleviate the risk of extinction through the establishment of populations in locations from which invasive predators have been removed. But do translocations represent a viable strategy for reptile conservation? We investigate the numerical and genetic outcomes of translocations of reptiles as reintroductions to islands cleared of introduced mammals around New Zealand. These reintroductions included nine populations of tuatara ( Sphenodon punctatus ), ten populations of six species of geckos and 24 populations of 12 species of skinks on a total of 24 islands. Reintroduced populations are often relatively small, which exposes them to associated demographic and genetic problems. We compared criteria for success based on abundance with available genetic data for four species of reintroduced reptiles. Three populations of skinks showed some loss of genetic heterozygosity but have nonetheless met most criteria for numerically viable populations. Whether loss of genetic variability might have long-term consequences for persistence is unclear because the genetic basis for population viability is still debated. We found that the success of reintroductions can be influenced by complex interactions between numerical, genetic and administrative constraints on project design. We thus suggest that obtaining data on the outcomes of reptile recovery will require managers to avoid mixing populations for pre-emptive genetic rescue, and a commitment to long term ecological and genetic studies. Graphical abstract: Highlights: Invasive mammals threaten reptiles on islands but mammal removal is increasing. Reptiles have been reintroduced to 24 New Zealand islands cleared of alien mammals. Numerically based criteria for successful reintroductions ignore genetic issues. Reintroduced lizards are established despite some loss of genetic heterozygosity. Reintroductions involved interplays of ecological, genetic and administrative issues.